Предмет: Математика,
автор: lora1306
1дм 2см+5дм 7см=
8м8дм-3м7дм=
6дм8см+2дм2см=
8дм6см+2дм2см=
8дм6см-59см=
4м7дм-37дм=
9дм3см-93см=
2дм7см+53см=
5дм6см+44см=
7м4дм+8дм=
Ответы
Автор ответа:
0
8м8дм-3м7дм
1м=10дм
88дм-37дм=51дм = 5м1дм
6дм8см+2дм2см
1дм=10см
68см+22см=90см = 9дм
8дм6см+2дм2см
1дм=10см
86см+22см=108см =10дм8см = 1м8см
8дм6см-59см
1дм=10см
86см-59см=27см = 2дм7см
4м7дм-37дм
1м=10дм
47дм-37дм=10дм = 1м
9дм3см-93см
1дм=10см
93см-93см=0
2дм7см+53см
1дм=10см
27см+53см=80см = 8дм
5дм6см+44см
1дм=10см
56см+44см=100см = 10дм = 1м
7м4дм+8дм
1м=10дм
74дм+8дм=82дм = 8м2дм
1м=10дм
88дм-37дм=51дм = 5м1дм
6дм8см+2дм2см
1дм=10см
68см+22см=90см = 9дм
8дм6см+2дм2см
1дм=10см
86см+22см=108см =10дм8см = 1м8см
8дм6см-59см
1дм=10см
86см-59см=27см = 2дм7см
4м7дм-37дм
1м=10дм
47дм-37дм=10дм = 1м
9дм3см-93см
1дм=10см
93см-93см=0
2дм7см+53см
1дм=10см
27см+53см=80см = 8дм
5дм6см+44см
1дм=10см
56см+44см=100см = 10дм = 1м
7м4дм+8дм
1м=10дм
74дм+8дм=82дм = 8м2дм
Похожие вопросы
Предмет: Английский язык,
автор: slpalzlL
Предмет: Қазақ тiлi,
автор: Ar1q
Предмет: Українська мова,
автор: sweettv58
Предмет: Литература,
автор: Аля17521